Os Extrativistas do caranguejo-uçá (Ucides cordatus) e o esforço pesqueiro na Reserva Extrativista Marinha Caeté- Taperaçu, Bragança-PA - CONCEIÇÃO, José Mateus Sousa (2021)
The present study on “The uçá crab (Ucides cordatus) extractivists and the fishing effort in the Caeté-Taperaçu Marine Extractive Reserve” brings field results through qualitative and quantitative research that meets the objectives: a) Map the transect made by the uçá crab fishermen, from the parameters of easy access (FA) and difficult access (DA), in the mangroves of the Caeté-Taperaçu Marine Extractive Reserve (Bragança-PA) and georeferencing the areas of easy and difficult access in crab fishing -uçá by means of GPS. The sample number (n) consisted of 8 fishermen, subdivided n = 2 from 18 to 30 years and n = 2 from 41 years of age onwards in the FA areas, and n = 2 from 18 to 30 years and n = 2 from 41 years old onwards in the areas of AD. The main results point out that crab scavengers are people who live in coastal- estuarine communities and appropriate and use environmental resources, especially the crab-uçá resource. In addition they demonstrate knowledge from the process of the crab resource food chain to the process of seedlings (walk). It also identified the planning process for the transects, namely: pre-entry, entry, extraction and exit, are elements that vary according to the territory to be explored, being the planning conditioned to environmental seasonality. It concludes, therefore, that extractivists have knowledge that can mediate the process of management and management of mangrove resources.